The Importance of Microscopic Examination of the Lungs in Decedents with Sustained Central Intravascular Catheters: A Nine‐Case Series1. Issue 2 (14th November 2014) - Hamilton, Heidi H.; Batalis, Nicholas I.; Presnell, Susan E.; Schandl, Cynthia A.; Tormos, Lee Marie
Abstract Indwelling intravascular catheters provide convenient access to healthcare personnel and also recreational intravenous drug users who inject suspensions of oral medications. A nine‐case series of autopsies of clinically stable decedents with indwelling catheters and sudden death is herein presented. Pulmonary histologic findings were consistent with intravenous administration of oral medications in all cases. In eight, the mechanism of death was directly attributed to occlusive vascular embolization of foreign material, with or without contribution of acute drug toxicity. In one, the mechanism of death was solely attributed to acute drug toxicity. Acute, massive embolization of foreign material may explain sudden death by vascular obstruction, whereas chronic repeated injections lead to obliteration of the pulmonary vasculature, increased pulmonary vascular resistance, and cardiac failure. Therefore, a complete autopsy with histologic examination of the lungs and toxicology testing is recommended in patients with indwelling catheters to determine the cause and mechanism of death.